First record of the genus Pentzia (Asteraceae) in Oman - Thulin, Mats; Patzelt, Annette (Phytotaxa, 2020)
Pentzia arabica, previously known only from a few collections from Yemen, is reported also from Jabal Samhan in Oman. This is the first record of a Pentzia in Oman, and the locality is the northernmost and easternmost known for the genus. A map of the distribution of P. arabica and its presumed sister species, P. somalensis in Somalia, is presented. Apart from these two species in the Horn of Africa region, the disjunct Pentzia comprises 26 species in southern Africa and two species in North Africa.